A new robot for flexible ureteroscopy: Development and early clinical results (IDEAL stage 1-2b) - Sağlam, Remzi; Rassweiler, Jens (European urology, 2014)
Background - An improved armamentarium has had a significant impact on the emerging role of flexible ureteroscopy (FURS) for the management of nephrolithiasis; however, FURS still represents a challenging technique. - Objective - To examine a robotic device designed for FURS for its impact on ergonomics and outcome of the procedure based on the IDEAL (idea, development, evaluation, assessment, long-term study) framework. - Design, setting, and participants - Roboflex Avicenna consists of a surgeon's console and a manipulator for the flexible ureterorenoscope. Following experimental evaluation of the prototype (IDEAL stage 1) and receipt of ethical approval, seven surgeons treated 81 patients (mean age: 42 yr [range: 6-68]) with renal calculi (mean volume: 1296±544 mm3 [range: 432-3100 mm3]) in an observational study (IDEAL stage 2). - Surgical procedure - Robotic FURS was performed with the Roboflex Avicenna robotic device. - Outcome measurements and statistical analysis - Numerical data were analysed with the Mann-Whitney test, and categorical variables were analysed using the chi-square test or Fisher exact test. P values <0.05 were considered statistically significant. - Results and limitations - Mean robot docking time was 59.6±45 s. Mean operative time was 74min (range: 40-182). Mean fragmentation speed was 29.1±6.1 mm3/min. Ergonomics based on a validated questionnaire showed significant advantage for robotic FURS (total score: 5.6 vs 31.3; p<0.01). A 10/12F-access sheath was used in 72 patients. Two cases required secondary FURS, one because of malfunction of the flexible digital ureteroscope and another because of larger residual fragments. In the remaining 79 cases, complete stone disintegration was accomplished. - Conclusions - Roboflex Avicenna provides a suitable and safe platform for robotic FURS with significant improvement of ergonomics. Future studies should evaluate its impact on the clinical outcome of FURS. - Patient summary - Robotic flexible ureteroscopy (FURS) was performed with the Roboflex Avicenna robotic device. Results showed that Roboflex Avicenna provides a suitable and safe platform for robotic FURS with significant improvement of ergonomics.
Gesehen am 05.11.2020